Novel inclusive search for the Higgs boson in the four-lepton final state at CDF - Aaltonen, T; Alvarez Gonzalez, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; Asaadi, J; et al. (2012)
An inclusive search for the standard model Higgs boson using the four-lepton final state in proton-antiproton collisions produced by the Tevatron at √s=1.96TeV is conducted. The data are recorded by the CDF II detector and correspond to an integrated luminosity of 9.7fb -1. Three distinct Higgs decay modes, namely ZZ, WW, and ττ, are simultaneously probed. Nine potential signal events are selected and found to be consistent with the background expectation. We set a 95% credibility limit on the production cross section times the branching ratio and subsequent decay to the four-lepton final state for hypothetical Higgs boson masses between 120GeV/c2 and 300GeV/c2. © 2012 American Physical Society.